1998
DOI: 10.1103/physrevlett.81.4361
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Structural Anisotropy in Optical Glasses Treated to Support Second Harmonic Generation

Abstract: Structural alterations in v-SiO2 induced by "thermal poling", a treatment which makes the glass able to double the frequency of an impinging infrared light, are revealed by neutron diffraction as a breakdown of the macroscopic isotropy. This leads to concomitant changes in the vibrational density of states measured by inelastic neutron scattering. The observations are found to be consistent with the emergence of partial ordering within the glassy matrix along the direction of an electrostatic field applied dur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
6
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
(16 reference statements)
3
6
0
Order By: Relevance
“…At the same time Alley et al [11] interpreted the proton conduction observed during poling, by a decrease of hydroxyl Si-OH bonds associated with an increase of non-bridging oxygen (Si-O À ). Simultaneously, an increase of less tensed Si-O-Si groups is observed perpendicularly to the poled surfaces which is in agreement with the results given by Cabrillo et al, illustrating the structural anisotropic modifications produced by the poling [30].…”
Section: Discussionsupporting
confidence: 92%
“…At the same time Alley et al [11] interpreted the proton conduction observed during poling, by a decrease of hydroxyl Si-OH bonds associated with an increase of non-bridging oxygen (Si-O À ). Simultaneously, an increase of less tensed Si-O-Si groups is observed perpendicularly to the poled surfaces which is in agreement with the results given by Cabrillo et al, illustrating the structural anisotropic modifications produced by the poling [30].…”
Section: Discussionsupporting
confidence: 92%
“…Although they appear randomly oriented in our measurements, the absolute orientation is lost during the abrasion process. The anisotropy previously observed by neutron diffraction 4 lends support to the possibility of a preferential orientation. However, the fact that the nonlinearity is mostly located a few microns below the anode surface makes it unlikely that the intrinsic (2) of the nanocrystals is the sole cause of the effect.…”
supporting
confidence: 50%
“…The estimate of the density of ionizable defects required to develop such a spacecharge is a mere few parts per million. Recently, neutron diffraction and inelastic scattering 4 have shown that the glass structure of ''poled'' silica plates as described by the g(r) radial distribution functions, becomes anisotropic and significantly differs from that of native samples. From data on hand at the time, crystallization of part of the glassy matrix into a cristobalite polymorph of silica appeared as a reasonable possibility.…”
mentioning
confidence: 99%
“…2 In most of the reported experiments on SHG in fused silica, the signal was regarded as essentially coming from a thin layer of a few microns depth near the anode surface. [1][2][3][4][5] However, according to Le Calvez, Freysz, and Ducasse, SH signal was also induced in the cathode surface area. 3 At the same time, the authors did not observe modulations in the Maker fringe pattern due to the interference of the SH signals generated from both surfaces of the poled glass sample.…”
Section: Introductionmentioning
confidence: 90%
“…4 They concluded to large microscopic alterations in the anodic poled region ͑about 5-m-deep below the anode surface͒ along the direction of the poling field, involving at least next nearest Si neighbors. They effectively evidenced an elongation of the shortest Si-Si distance from 3.06 to 3.23 Å in this direction and concluded to the opening of Si-O-Si bond angles in the same direction.…”
Section: Introductionmentioning
confidence: 98%